Implementasi Dakwah Melalui Pendidikan Pada Kaum Hu’afa: Studi Kasus Sekolah Smart Ekselensia Lembaga Pengembangan Insani Dompet Du’afa - Rubiyanah Rubiyanah; Abdul Jalil (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2019)
Da'wah is not only meant as tabligh activities. Activities that lead to actions or actions to move community groups with the aim of increasing the dignity and values of the people are also da'wah. DompetDhuafaPendidikan (DDP) through the Human Development Institution seeks to realize da'wah through education for the du'afa by establishing SMART EI, boarding high school, free of charge and accelerating (5 years of junior-high school). Based on this, the question arises, how is the implementation of da'wah through the education of du'afa conducted by Du'afa Wallet? This study uses qualitative research, with data collection techniques through observation, interviews with leaders, teachers and student beneficiary representatives, as well as through documentation. Data is presented by descriptive analysis method. The manifestation of DompetDhuafa's concern,which isto educate the nation's life and to improve the quality of human resources of Muslims in Indonesia, is implemented through the Junior High School and Senior High School programs under the Human Development Institute which is focused on dhu'afa children. The reason why the focus is on students from among the dhu'afa, because not all educational institutions can accept students who are financially unable to pay for education. Moreover, superior schools that have qualities that are globally competitive, can certainly not be followed by those who have economic limitations, despite achieving.